2009
DOI: 10.1021/jp908669u
|View full text |Cite
|
Sign up to set email alerts
|

WO3 Nanoparticles in the 5−30 nm Range by Solvothermal Synthesis under Microwave or Resistive Heating

Abstract: WO3 nanoparticles in the 5−30 nm range have been prepared by solvothermal treatment of tungsten chloride in benzyl alcohol up to 210 °C followed by annealing in air. The solvothermal treatment has been performed by resistive or microwave heating and leads to agglomerates of tungsten oxide nanoparticles covered by organic residues. As determined by thermogravimetric measurements in air, the organic residues have been removed at 350 °C for samples prepared by microwave heating and at least at 420 °C for those pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 30 publications
5
45
0
Order By: Relevance
“…When the XRD patterns of the samples were compared to tungsten oxide JCPD files (No. 43-1035) and those reported by others [23,24], the diffraction patterns of the samples assigned those of WO 3 monoclinic structure. No significant differences were observed in the XRD peaks between the WO 3 and Pd/WO 3 samples, indicating that the Pd doping did not influence the crystal structures of WO 3 .…”
Section: Characterizationsupporting
confidence: 65%
“…When the XRD patterns of the samples were compared to tungsten oxide JCPD files (No. 43-1035) and those reported by others [23,24], the diffraction patterns of the samples assigned those of WO 3 monoclinic structure. No significant differences were observed in the XRD peaks between the WO 3 and Pd/WO 3 samples, indicating that the Pd doping did not influence the crystal structures of WO 3 .…”
Section: Characterizationsupporting
confidence: 65%
“…While the first step followed the common ether eliminationm echanism (Scheme 5c), in an ext step the formed tungsten oxide nanowires catalyzed the polymerization of benzyla lcohol into polyphenylene methylene (Figure 5a) under their incorporation into the polymer,f orming an inorganic-organic hybrid monolith (Figure 5b). [47] As imilar polymerization reaction was also observed in the WCl 6 -benzyl alcohol [161][162] and in the FeCl 3 -benzyl alcohol system. [144] Interestingly,i tw as found that the resulting polymer polyphenylene methylene exhibits pronounced blue fluorescence in spite of the fact that the methylene group prevents full conjugation.…”
Section: Reactions Betweenmetal Halides and Alcohols Or Ethersmentioning
confidence: 70%
“…They have also shown orthorhombic and hexagonal phases of WO 3 at pH 0.4 and pH 1.8 in the presence of Na 2 SO 4 as SDA . Houx et al have prepared 5–30 nm size different crystal structures of WO 3 nanoparticles by solvothermal treatment of tungsten chloride in benzyl alcohol up to 210 °C followed by annealing in air . Ultrafine uniform diameter (≈5 nm) WO 3 nanoparticles are synthesized by nanocasting route, in the channels of the mesoporous silica template .…”
Section: Introductionmentioning
confidence: 99%